2021
DOI: 10.7759/cureus.16792
|View full text |Cite
|
Sign up to set email alerts
|

Identifying Risk Factors for Complications During Exposure for Anterior Lumbar Interbody Fusion

Abstract: Introduction An anterior approach to lumbar interbody fusion is a widely utilized method of access to the lumbar spine. Due to the potential for vascular complications with spine exposure, vascular surgeons are frequently included in the care of these patients as part of a team-based approach. Identifying risk factors for such complications is difficult and not well-defined in the literature. In this investigation, we evaluate the potential risk factors for complications during anterior lumbar inter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
5
0
5

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 20 publications
3
5
0
5
Order By: Relevance
“…Rates of vascular injury vary between different studies. A recent review found a venous injury rate of 10.4%, similar to the rate we found in our study [ 20 ]. Another review reports a wide range of vascular injury rates, from 0% up to 18.1%, with arterial injuries being less frequent than venous lacerations [ 21 ].…”
Section: Discussionsupporting
confidence: 92%
“…Rates of vascular injury vary between different studies. A recent review found a venous injury rate of 10.4%, similar to the rate we found in our study [ 20 ]. Another review reports a wide range of vascular injury rates, from 0% up to 18.1%, with arterial injuries being less frequent than venous lacerations [ 21 ].…”
Section: Discussionsupporting
confidence: 92%
“…Age showed a strong positive correlation with elevated BL. Other studies have supported this [ 6 , 15 ]. We postulate this is due to diminution of the supportive perivascular connective tissues which renders the small vessels more prone to disruption.…”
Section: Discussionsupporting
confidence: 76%
“…[22][23][24][25][26] Male sex, older age, history of previous abdominal surgery and prior spinal instrumentation are associated with additional risk. 27,28 Our review findings were in keeping with these data, as 81.8% of the subset of patients with venous injury during anterior spinal exposures had undergone prior lumbar surgery. Given this well described risk, obtaining routine pre-operative evaluation of vessel anatomy with imaging as well as utilization of a vascular surgeon to assist with exposure may be beneficial.…”
Section: Discussionsupporting
confidence: 67%